Climate reporting in the fast lane? The impact of corporate governance on the disclosure of climate-related risks and opportunities - Maria Gebhardt; Anne Schneider; Florian Siedler; Philipp Ottenstein; Henning Zülch (Business Strategy and the Environment, 2024)
Abstract Climate-related issues have become increasingly relevant, as reflected in current political and academic discourse. This development is also reflected in investors' capital allocation decisions and their demand for climate-related information. Considering the recommendations of the Task Force on Climate-related Financial Disclosures (TCFD), we first investigate the climate-related disclosure quality of listed German firms. We use self-constructed scoring models based on the TCFD recommendations to measure disclosure quality. Second, we use regression analysis to investigate whether corporate governance can explain climate-related disclosure quality. The results indicate that disclosure quality is heavily dispersed across firms, with risk disclosure being better than disclosure of opportunities. Corporate governance factors exert distinct but mostly weak influence on climate-related disclosure quality and that institutional ownership promotes climate-related disclosure quality. We show several implications for research and practice and highlight the relevance for firms to implement a comprehensive approach to communicating climate-related issues.
Keywords: 330; climate-related disclosure quality; climate-related opportunities; climate-related risks; corporate governance; institutional ownership; Task Force on Climate-related Financial Disclosures (TCFD)